Ascariosis y su relación con la malnutrición en niños de 2 a 10 años. Sector “Galo Vera”. Cantón Ventanas. Provincia Los Ríos. Periodo septiembre 2017–febrero 201 - Vaca Segura, Paola Fernanda (2018)
The problems of parasitosis are some of the main pathologies that affect children under 20, this has generated research into the causes and effects produced in the body will increase in recent years. This investigation is in the sector Galo Vera del Cantón Ventanas, province of Los Ríos, in the period September 2017 - February 2018, regarding the topics of ascariosis and its relationship with malnutrition in children from 2 years to 10 years, has made it possible to identify the predisposing factors for there to be an incidence of this pathology. Therefore, in the field study it was determined that the main problem for the relationship between the two is subject to the problems of health and personal hygiene, as well as the consumption of junk food that produces a state of nutrition in them. appropriate. The result of all this was that it was possible to show that 49% of the children most affected were children who were not of school age and who usually had greater attention from parents. In this sense, it can be determined that the most viable alternative to counteract this problem is the design of a training program on standards of health and personal and family hygiene, as well as a balanced diet to achieve a good life, as defined by the country's policies.